Simulation of the furnace of the boiler P-49 in the package of applied programs fire 3D; MATEC Web of Conferences; Vol. 110 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment (HMTTSC 2017) - Tsibizov E. Evgeny (2017, 2017)
Title screen